Structural changes induced in waxy maize starch and normal wheat starch by maltogenic amylases - Grewal, Navneet Kaur (Kansas State University, 2014)
Maltogenic amylases are widely being used as an antistaling agent in baking industry. However, their action on starch in granular, swelled and dispersed forms, important components formed during bread baking, is largely unknown. Actions of two maltogenic amylases- A and -B on waxy maize starch (WMS) (100% amylopectin) and normal wheat starch (NWS) (~25% amylose) were studied and compared. For any given starch type, starch form, and hydrolysis time, maltogenic amylase-B hydrolyzed both starches more than maltogenic amylase-A as seen through sugar profile analysis indicating its higher degree of multiple attack action (DMA). Their action on non reducing ends blocked compound, p nitrophenol maltoheptaoside, confirmed their endo action. Maltogenic amylase-B showed a higher endo to total enzyme activity ratio than maltogenic amylase-A at any given enzyme weight. Greater MW reduction of dispersed starches by maltogenic amylase-B indicates its higher level of inner chain attack (LICA). Interestingly, MW distributions profiles of swelled starch hydrolysates did not show significant differences irrespective of swelling temperatures. Both enzymes showed differences in oligosaccharides compositions in dispersed and swelled starches’ reaction mixtures with sugars of degree of polymerization (DP) > 2 being degraded to glucose and maltose during later stages. For granular starches, enzymes followed a random pattern of formation and degradation of sugars with DP >2. MW distributions of hydrolyzed granular starches did not show significant shift until at the end of 24h when a low MW peak was observed. Morphological study of granular starches showed that maltogenic amylase-A mainly caused pinholes on WMS while maltogenic amylase-B caused surface corrosion with fewer pinholes. For NWS, both enzymes degraded A granules with deep cavities formation during later stages. A decrease in crystallinity of granular starches means that enzymes were able to hydrolyze both amorphous and crystalline regions. These results indicate that maltogenic amylase-B with a high LICA and high DMA possesses a better starch binding domain which can decrease the starch MW without affecting bread resilience. Strucuture of maltogenic amylase-A modified amylopectin (AP) in relation to its retrogradation was also studied. AP retrogradation was completely inhibited at % DH ≥ 20. MW and chain length distributions of debranched residual AP indicated with increase in % DH, a high proportion of unit chains with DP ≤ 9 and low proportion of unit chains with DP ≥ 17 were formed. Higher proportion of short outer AP chains which cannot participate in double helices formation supports the decrease and eventually complete inhibition of retrogradation. Thus, maltogenic amylase-A can play a very powerful role in inhibiting starch retrogradation even at limited DH (%).
Keywords: Maltogenic amylase; Starch retrogradation; Baking; Food Science (0359)